Very High CA125 due to Non-neoplastic Lesion of Ovary - Bista, KDB (Nepal Journal of Obstetrics and Gynaecology, 2014)
High CA-125 levels have been strongly associated with ovarian malignancy. But due to nonspecific nature of this tumor marker it has been found to be raised to high levels above 1000u/Ml even in some non neoplastic conditions which have to be kept in mind. A young woman was found to have very high Ca125 levels of 3500u/Ml after rupture of endometrioma. Endometrioma, pelvic inflammatory disease, abdominal tuberculosis are some of the nonneoplastic conditions associated with very high levels of Ca125. DOI: http://www.dx.doi.org/10.3126/njog.v7i2.11146 Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 2 / Issue 14 / July-Dec, 2012 / 52-54